Fish in Faith: Exploring Symbol as Survival Strategies in Christianity - Suprianto, Bibi; Alfian, Andi; Kristanto, David (UIN Sunan Gunung Djati Bandung, 2022)
This study explores the history of one of the important symbols in the Christian tradition, namely the history of the fish symbol. This study argues that the fish symbol is one of the survival strategies for Christians to survive and contest with other groups in the socio-religious context at that time. Thus, this study formulates research questions such as how is the history of fish in the Christian tradition? How does the fish symbol become a medium of survival and resistance? Does the fish symbol have any relevance in the history of Christianity in Indonesia? This research uses literature study, which means relying on written literature discussing fish symbolism in Christianity's history. The results of this study indicate that the symbolization of fish in Christian history can not only be seen from the theological aspect but also from the socio-historical aspect as a survival strategy. Furthermore, the research material is structured with the following framework: the first part discusses the history and meaning of the fish symbol as a savior and unifier in ancient Christianity; the second part discusses the symbolic significance of fish as the spread of Christianity in Indonesia; the third part, symbolism as a strategy to survive both in the form of acculturation and religious-cultural identification in the context of religion and culture. In short, the symbolism of fish in the Christian tradition is very complex, containing theological content and historical-social-cultural. By understanding how symbolization works in religious traditions, we, therefore, can understand how religion in all its aspects developed from the past to the present, and also to the future.